WRITING MATERIAL FOR OFFICE ADMINISTRATION STUDY PROGRAM IN VOCATIONAL HIGH SCHOOL: STUDENTS’ NEED ANALYSIS - Iga Yolanda; N. Ngadiso; S. Sumardi (Journal of English Education, 2018)
Vocational High School is course with aim to prepare the students to have specific skills by having practical activities based on its study program. It has the same purpose with English for specific purposes (ESP) course which aims to meet the students’ specific language need. ESP courses help students to use English appropriately as well as accurately to perform their jobs in a various situations where they encounter their English language function. ESP course often begins with the students’ need. Students’ need analysis is needed to be identified to be able to meet the effective learning material based on what the students really need. This study aims to investigate the writing materials needs of eleventh grade students of Office Administration study program in Vocational High School from viewpoints of students. This study used descriptive qualitative analysis with questionnaire and interview method to collect the data. The subjects of the research were eleventh grade of Office Administration students that consisted of 34 students by using purposive sampling. The result indicated that the students have several needs in terms of target needs and learning needs. Target needs are divided into necessities, wants, and lacks. Based on the result of target needs, the students are lack of component of writing skills including express ideas, write with correct organization, use correct grammar, punctuation, capitalization, and spelling, and use appropriate vocabulary based on the context of the text. Thus, the students need and want to learn those components of writing skills. Meanwhile, learning needs are divided into input, procedure, setting, and accessibility. The input is divided into content of materials, activities, and design. The teachers should pay attention more on those aspects to fulfill the students’ need to help them transition successfully to their future careers after graduation.